Envolvimento do receptor TRPA1 na resposta inflamatória induzida pela administração tópica de cinamaldeído em camundongos - Silva, Cássia Regina da (2011)
Cinnamaldehyde, a natural compound frequently present in cosmetic formulations, induces skin irritation when topically applied, but the mechanism by which cinnamaldehyde produces such skin reactions is unclear. Here, we showed that cinnamaldehyde induced ear edema in mice (1-6 μg/ear) with a maximum effect with 4 μg/ear (Emax of 0.18 ± 0.02 mm and an ED50 value of 2.0 (1.1- 3.4 μg/ear). Cinnamaldehyde can induce leukocyte infiltration detected by an increase in MPO activity and confirmed by histological analyses. The edema and cellular infiltration evoked by 4 μg/ear of cinnamaldehyde was prevented through topical application of ruthenium red, a non selective TRP antagonist or by camphor and HC030031, two TRPA1 receptor antagonists. In contrast, the edema and the leukocyte infiltration was unaffected by the TRPV1 receptor antagonist SB366791. Cinnamaldehydeinduced edema but not cellular infiltration was also prevented though topical application of the tachykinin NK1 antagonist aprepitant, indicating a neuropeptides release phenomenon in this process. Also, we observed that repeated topical applications of cinnamaldehyde (4 μg/ear) did not induced sensitization/desensitization alterations. Interestingly, the TRPV1 antagonist, capsaicin, repeated treatment abrogated its edematogenic response, confirming the desensitization process and decrease partially the cinnamaldehyde induced edema, suggesting the involvement of capsaicin-sensitive fibers and additional targets in cinnamaldehyde response. The present results demonstrated that cinnamaldehyde induces mouse skin inflammation through a mechanism involved the TRPA1 receptor activation and subsequent leukocyte infiltration. In addition, evidence supports the assumption that the tachykinin NK1 receptor is involved in these inflammatory responses.